2015
DOI: 10.1159/000430301
|View full text |Cite
|
Sign up to set email alerts
|

Interaction Between IGF1 Polymorphisms and the Risk of Acute Lymphoblastic Leukemia in Chinese Children

Abstract: Background/Aims: IGF1 is a key regulator in cell proliferation and apoptosis, and the 3' un-translated region (3'UTR) of the gene plays an important role in gene expression. For the first time, we explored the relationship between polymorphisms in the IGF1 3'UTR region and the risk of childhood acute lymphoblastic leukemia (ALL). Methods: Questionnaires were applied to collect epidemiological data. The genotypes of IGF1 polymorphisms were tested in a population of 744 ALL patients and 1088 cancer-free controls… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
16
0

Year Published

2016
2016
2020
2020

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 14 publications
(17 citation statements)
references
References 55 publications
(60 reference statements)
1
16
0
Order By: Relevance
“…In agreement with our results, Lu et al (2015) demonstrated that the trend in IGF-1 mRNA level was upward with the addition of variant A allele of rs6214 SNP, but the difference was not statistically significant.…”
Section: Discussionsupporting
confidence: 90%
“…In agreement with our results, Lu et al (2015) demonstrated that the trend in IGF-1 mRNA level was upward with the addition of variant A allele of rs6214 SNP, but the difference was not statistically significant.…”
Section: Discussionsupporting
confidence: 90%
“…New targets and therapy strategies against leukemia are still of intense interest [40-42]. Zinc plays dual roles in regulating cell proliferation and apoptosis.…”
Section: Discussionmentioning
confidence: 99%
“…Myelodysplastic syndrome (MDS) is used as a prime example of the veracity of the SMT by its proponents but we have learned that risk stratification is needed and that the evolution of risk for leukemia is "...less than 10% at 15 years for patients with low-risk MDS compared with more than 50% at 1 year for those with high-risk disease" [37]. Further acute lymphoblastic leukemia (ALL) is thought of as being caused by genetic factors, such as mutations or polymorphisms and environmental exposures; a minority of ALL in children was associated with polymorphisms of rs17251221, rs4946936 or rs6214 and rs6218 in the 3'UTR of insulin-like growth factor 1 (IGF1) [38][39][40]. Recently it was shown, that ALL cases are not inherited.…”
Section: Somatic Mutation Theorymentioning
confidence: 99%